2019
DOI: 10.1371/journal.pone.0220186
|View full text |Cite
|
Sign up to set email alerts
|

Factors that predict life sciences student persistence in undergraduate research experiences

Abstract: Undergraduate research experiences (UREs) have the potential to benefit undergraduates and longer UREs have been shown to lead to greater benefits for students. However, no studies have examined what causes students to stay in or consider leaving their UREs. In this study, we examined what factors cause students to stay in their UREs, what factors cause students to consider leaving their UREs, and what factors cause students to leave their UREs. We sampled from 25 research-intensive (R1) public universities ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

5
93
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 69 publications
(108 citation statements)
references
References 73 publications
5
93
0
1
Order By: Relevance
“…Seymour and Hewitt (1997) pointed out the crucial role of motivational aspects in STEM retention, stating that losing interest and motivation to engage in STEM-related activities is the most common reason for students' decision to switch away from STEM majors. Although student gains and outcomes of undergraduate research (UR) experience have been well-discussed in the literature, systematic and empirical research to clarify the motivational factors, perceived drivers, and barriers of the processes of the research programs is limited (Adedokun, Bessenbacher, Parker, Kirkham, & Burgess, 2013;Cooper et al, 2019;Gardner, Forrester, Jeffrey, Ferzli, & Shea, 2015;Linnenbrink-Garcia et al, 2018). Mostly, evaluation and research studies regarding UR experience focus on reporting program outcomes with less emphasis have been put on exploring contextual factors (e.g., the design of the program and institutional features), sociocultural factors (e.g., socialization, mentor-student relationship), and participants' psychological factors (e.g., motivational beliefs) (Adedokun et al, 2013;Linnenbrink-Garcia et al, 2018).…”
mentioning
confidence: 99%
See 3 more Smart Citations
“…Seymour and Hewitt (1997) pointed out the crucial role of motivational aspects in STEM retention, stating that losing interest and motivation to engage in STEM-related activities is the most common reason for students' decision to switch away from STEM majors. Although student gains and outcomes of undergraduate research (UR) experience have been well-discussed in the literature, systematic and empirical research to clarify the motivational factors, perceived drivers, and barriers of the processes of the research programs is limited (Adedokun, Bessenbacher, Parker, Kirkham, & Burgess, 2013;Cooper et al, 2019;Gardner, Forrester, Jeffrey, Ferzli, & Shea, 2015;Linnenbrink-Garcia et al, 2018). Mostly, evaluation and research studies regarding UR experience focus on reporting program outcomes with less emphasis have been put on exploring contextual factors (e.g., the design of the program and institutional features), sociocultural factors (e.g., socialization, mentor-student relationship), and participants' psychological factors (e.g., motivational beliefs) (Adedokun et al, 2013;Linnenbrink-Garcia et al, 2018).…”
mentioning
confidence: 99%
“…Much of the literature on STEM persistence, using either concurrent or retrospective reports indicated that students in STEM majors listed interest and enjoyment as the primary reasons for their persistence in STEMrelated activities (Lopatto, 2010;McGee & Keller, 2007;Meaders et al, 2020;Seymour & Hewitt, 1997;Seymour, Hunter, Laursen, & DeAntoni, 2004). For instance, students who indicate having a positive lab environment and enjoying everyday research tasks were more likely to continue their research experience (Cooper et al, 2019;Mabrouk & Peters, 2000;Perez, Cromley, & Kaplan, 2014) and link the perceived value of their experience to their personal and professional gains (Mabrouk & Peters, 2000;Seymour et al, 2004;Thiry, Laursen, & Hunter, 2011). On the other hand, students who leave their UR may not value engaging in research or may perceive high costs on staying in their UR (Cooper et al, 2019;Linnenbrink-Garcia et al, 2018).…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…Labs include computer and bench work, with all benchwork following BSL2 Laboratory Safety Guidelines due to the presence of unknown microorganisms. Overall, CUREs improve student access to research opportunities and persistence in STEM; additionally, they incorporate outreach and interdisciplinary studies (10)(11)(12)(13)(14)(15)(16). CURE students are motivated to develop novel research questions, conduct basic microbiology lab processes, analyze and interpret data, and communicate scientific findings through written and oral presentations to their peers and the broader university community (17,18).…”
Section: As a Component Of The Southern Association Of Colleges And Smentioning
confidence: 99%